A specific fungal transcription factor controls effector gene expression and orchestrates the establishment of the necrotrophic pathogen lifestyle on wheat - Jones, Darcy; John, Evan; Rybak, Kasia; Phan, Huyen T. T.; Singh, Karam; Lin, S.Y.; Solomon, P.S.; Oliver, Richard; Tan, Kar-Chun (NATURE RESEARCH, 2019)
The fungus Parastagonospora nodorum infects wheat through the use of necrotrophic effector (NE) proteins that cause host-specific tissue necrosis. The Zn Cys transcription factor PnPf2 positively regulates NE gene expression and is required for virulence on wheat. Little is known about other downstream targets of PnPf2. We compared the transcriptomes of the P. nodorum wildtype and a strain deleted in PnPf2 (pf2-69) during in vitro growth and host infection to further elucidate targets of PnPf2 signalling. Gene ontology enrichment analysis of the differentially expressed (DE) genes revealed that genes associated with plant cell wall degradation and proteolysis were enriched in down-regulated DE gene sets in pf2-69 compared to SN15. In contrast, genes associated with redox control, nutrient and ion transport were up-regulated in the mutant. Further analysis of the DE gene set revealed that PnPf2 positively regulates twelve genes that encode effector-like proteins. Two of these genes encode proteins with homology to previously characterised effectors in other fungal phytopathogens. In addition to modulating effector gene expression, PnPf2 may play a broader role in the establishment of a necrotrophic lifestyle by orchestrating the expression of genes associated with plant cell wall degradation and nutrient assimilation. 2 6